Cyclosporin treatment does not impair the release of nitric oxide in human coronary arteries. Issue 3 (September 1991) - O'Neil, G S; Chester, A H; Kushwaha, S; Rose, M; Tadjkarimi, S; Yacoub, M H
Abstract : OBJECTIVE--It has been hypothesised that compromised endothelial function can contribute to the toxic manifestations associated with cyclosporin therapy. In vitro animal studies have implicated inhibition of release of the endothelium derived relaxing factor, nitric oxide; however, this has not been investigated in human tissue. The present study investigated the effect of cyclosporin A on nitric oxide release in human coronary arteries. DESIGN--Study of in vitro organ bath preparations and in vivo angiographic measurements in the coronary circulation. PATIENTS--For the in vitro experiments coronary arteries were harvested from the excised hearts of 10 patients requiring transplantation for reasons other than ischaemic heart disease. Three of these patients were being re-transplanted for obliterative bronchiolitis and had been receiving cyclosporin for a mean of 22 months. The in vivo study was performed on a group of 12 cardiac transplant recipients who were clinically well 1-5 years postoperatively and were not undergoing allograft rejection at the time of assessment. RESULTS--Isolated vessel segments in vitro relaxed in a dose dependent manner in response to substance P (10(-11)-10(-7) mol/l). The maximum response was 76.6 (7.4)% of the response to 1 microgram/ml glyceryl trinitrate. Incubation with 1000 and 2000 ng/ml cyclosporin reduced the response to 63.0 (11.5)% and 62.2 (11.1)% respectively; this was not statistically significant. In segments taken from the explanted hearts of three patients requiring re-transplantation, the mean maximum response was 78.0 (11.0)% and there was no correlation between maximum response in segments from each patient and the duration of cyclosporin therapy. The effect of intracoronary substance P in 12 cardiac transplant recipients was also examined (mean cyclosporin blood concentration 228.9 (42.8) ng/ml). The mean maximum dilatations measured as the percentage diameter change induced by substance P and isosorbide dinitrate were 22.1 (3.2)% and 26.0 (2.5)% respectively. There was no correlation between the degree of endothelium mediated vasodilatation in response to substance P and cyclosporin concentration. CONCLUSIONS--The nitric oxide response was preserved in the coronary arteries of patients exposed to cyclosporin. The mechanisms that initiate cyclosporin associated toxicity remain to be elucidated.